IMPACT ANALYSIS OF ALUMINUM HONEYCOMB SANDWICH PANEL BUMPER BEAM: A REVIEW - Pradip R. Lande; Rajesh V. Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
Bumper is a energy absorbing protective element which absorb the energy in front collision and protect valuable parts like radiator etc. Bumper is act like protective shield generally made of steel material. As economic point of view and to reduce consumption of fuel manufacturing of light weight vehicle is requirement of current situation. Application of composite material in automobile sector is now day common thing. Aluminum honeycomb sandwich panel is basically material from aerospace industries and known for its high strength to weight ratio. Sandwich structure basically having its properties due to geometry. To determine various properties of sandwich structure conducting experiments is expensive, so generally FEA is used .However complex geometry is hurdle so there are various theories are available for simplification of model.